2013
DOI: 10.1007/s10637-013-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

ZRX1, the first EGFR inhibitor-capecitabine based combi-molecule, requires carboxylesterase-mediated hydrolysis for optimal activity

Abstract: Capecitabine, an orally available prodrug of 5-FU, requires activation by carboxylesterase (CES) enzymes present in the liver to generate 5'-deoxy-5-flurocytidine ribose (5'-DFCR). The deamination of the latter by cytidine deaminase gives 5'-deoxy-5-fluorouridine ribose (5'-DFUR). Finally, the conversion of 5'-DFUR to the cytotoxic drug 5-FU, occurs primarily in the tumour and is catalyzed by thymidine phosphorylase (TP). Accordingly, it was surmised that events associated with an increase of TP levels should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Anti‐colon cancer drug CPT‐11 can be metabolize by CES 2 that is a subtype of CES, to produce the active metabolite SN‐38. The excessive accumulation of the latter in the intestinal tract results in severe diarrhea, therefore, the inhibition on CES 2 to reduce this side effect has become a research topic (Ait‐Tihyaty, Rachid, Larroque‐Lombard, & Jean‐Claude, 2013; Aizawa et al, 2003; Humerickhouse, Lohrbach, Li, Bosron, & Dolan, 2000; Small et al, 2010). 5 β ,29‐Dihydroxy alisol A ( 59 ), obtained from A. orientale , inhibited CES 2 with an IC 50 value of 29.2 μM, and the underlying mechanism between 59 and CES 2 was studied by molecular docking, all of which revealing the presence of hydrogen bond interactions with Glu77, Ser80, IIe446, and Lys447 and a lowest binding free energy of −3.94 kcal/mol (Wang et al, 2019).…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…Anti‐colon cancer drug CPT‐11 can be metabolize by CES 2 that is a subtype of CES, to produce the active metabolite SN‐38. The excessive accumulation of the latter in the intestinal tract results in severe diarrhea, therefore, the inhibition on CES 2 to reduce this side effect has become a research topic (Ait‐Tihyaty, Rachid, Larroque‐Lombard, & Jean‐Claude, 2013; Aizawa et al, 2003; Humerickhouse, Lohrbach, Li, Bosron, & Dolan, 2000; Small et al, 2010). 5 β ,29‐Dihydroxy alisol A ( 59 ), obtained from A. orientale , inhibited CES 2 with an IC 50 value of 29.2 μM, and the underlying mechanism between 59 and CES 2 was studied by molecular docking, all of which revealing the presence of hydrogen bond interactions with Glu77, Ser80, IIe446, and Lys447 and a lowest binding free energy of −3.94 kcal/mol (Wang et al, 2019).…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…Compared with hCE1, hCE2 is expressed mainly in the gastrointestinal tract and at a relatively low level in the liver. hCE2 preferentially catalyzes substrates with a large alcohol group and a small acyl group, such as antitumor drugs irinotecan (CPT‐11; Hatfield et al, ), capecitabine (Ait‐Tihyaty, Rachid, Larroque‐Lombard, & Jean‐Claude, ), the anticoagulant prasugrel (Williams et al, ), and antiandrogen flutamide (Goda et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical use of CPT‐11 is limited by its side effects, especially life‐threatening delayed diarrhea that is mainly induced by the cytotoxicity of SN‐38 in the intestinal epithelial cells (S. J. Chen et al, ; Fujita, Kubota, Ishida, & Sasaki, ). Capecitabine, another antitumor prodrug, is metabolized first by hCE2 and then by other enzymes to 5‐fluorouracil, which is cytotoxic and frequently causes intestinal mucositis (Ait‐Tihyaty et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 We and others have shown that inhibition of the epidermal growth factor receptor with the clinical drug gefitinib leads to an increase in TP levels in BC cells. 25 – 27 It has also been demonstrated that high tumoral TP activity may serve as an indicator of response to fluoropyrimidine therapies. 28 Due to the contradictory role of TP reported in the literature, targeting TP as a rationale for anticancer therapy or establishing its use as a biomarker remains unclear.…”
Section: Introductionmentioning
confidence: 99%